Fresno County Revenue and Reimbursement Department Staff - Watkins, Howard::::::::: (1987)
Chief Assistant Leslie Silva at her desk with law books; Microfilm reader in background Corded desk telephone, 2-hole punch, paper clip dispenser, name plate, In/Out basket on desk